Cobro de intereses moratorios devengados durante la impugnación de deuda tributaria y derecho al debido procedimiento del deudor tributario - Campos López, Diego Alexander (2017)
This investigation has as source the intimidation and conditioning, that the tributary debtor suffers, to be able to interpose an impugnation as a resource in a tributary contentious procedure, due to the no suspension of the moratorium interest charge, from the Tributary Administration, until the resolution of the same resource; violating the defense right, in which is included the correct procedure right and impugnation, fundamental rights that are protected by the constitution. That situation leads to the study of several resolutions made by the resolution office of the last instance of the Tributary Administration (Tax court), using the deductiveinductive and analytic-synthetic method, furthermore the usage of the documental analysis technique using the data registration form, as an instrument for the data recollection, to get the results. In the same way, was made, the study of the tributary normative like the Tributary Code and its modifications, the law of General Administrative Procedure and its modifications and the Political Constitution of Peru from 1993, to dote this investigation of theoretical and doctrinaire fundaments in order to get the correspondent conclusions